Triple Trouble for Rupert - Parkinson, Ethelyn M. (USA SCHOLASTIC BOOK SERVICES, 1960)
Triple trouble for Rupert Back with his pals at the "No Dames Corner" of the Lincoln School. This time Rupert and his friends build a UNIVAC. But its the kind the gives a boys mother sensible answers. They dream up a hobby show and his mother sends in Ruperts picture as the prettiest baby?
Keywords: Children Literature